Depression, antidepressant use, and the risk of type 2 diabetes: a nationally representative cohort study - Kim, Hyewon; Lee, You-Bin; Lee, Jungkuk; Kang, Dongwoo; Kim, Gyuri; Jin, Sang-Man; Kim, Jae Hyeon; Hur, Kyu Yeon; Jeon, Hong Jin (Frontiers in Psychiatry, 2023)
Background: Previous studies have reported that depression can increase the risk of type 2 diabetes. However, they did not sufficiently consider antidepressants or comorbidity. Methods: The National Health Insurance Sharing Service database was used. Among the sample population, 276,048 subjects who had been diagnosed with depression and prescribed antidepressants (DEP with antidepressants group) and 79,119 subjects who had been diagnosed with depression but not prescribed antidepressants (DEP without antidepressants group) were found to be eligible for this study. Healthy controls (HCs) were 1:1 matched with the DEP with antidepressants group for age and sex. We followed up with them for the occurrence of type 2 diabetes. Results: In the group of DEP with antidepressants, although the risk of type 2 diabetes increased compared to HCs in crude analysis, it decreased when comorbidity was adjusted for. In the group of DEP without antidepressants, the risk of type 2 diabetes decreased both in the crude model and the adjusted models. The risk varied by age group and classes or ingredients of antidepressants, with young adult patients showing an increased risk even in the fully adjusted model. Conclusions: Overall, those with depression had a reduced risk of type 2 diabetes. However, the risk varied according to the age at onset, comorbidity, and type of antidepressants.